Implications of Renewal System of Criminal Justice Based on the Principles of Restorative Justice on The Role of Probation and Parole Officer - Moch. Fauzan Zarkasi; Nur Azisa; Haeranah Haeranah (UIN Sunan Gunung Djati, 2022)
In Indonesia, criminal law reform is manifested in plans to amend several laws and regulations, including the Criminal Code, the Criminal Procedure Code, and the Correctional Law. In addition, several criminal justice sub-systems have issued policy regulations that put forward the principle of penal mediation to accommodate the limitations or shortcomings of formal criminal law in resolving criminal cases. These various steps of change put forward a value known as restorative justice. The concept of restorative justice, which contains two main principles, namely participation, and recovery, always requires the role of Probation and Parole Officer as stated in the Law of the Republic of Indonesia Number 11 of 2012 concerning the Juvenile Criminal Justice System. The formulation of the following research problem is how the implications of reforming the criminal justice system based on the principles of restorative justice on the role of the Probation and Parole Officers. The purpose of this study was to determine the projected implications of reforming the criminal justice system based on the principles of restorative justice on the role of Probation and Parole Officers. This research is descriptive normative legal research. The results of the study indicate that Probation and Parole Officers have the potential to obtain strengthening of duties and functions in particular from the three main aspects of reform, namely strengthening alternative disposal, the existence of sentencing guidelines, as well as supervision and guidance in the implementation of various types of punishments and treatments. The expansion of these tasks and functions indicates the urgency of optimizing the fulfillment of technical and facilitative needs for the Probation and Parole Officers.